Depression in the Paediatric Population: Current Therapeutic Context and Challenges to Innovation - Rodrigues, Ana Rita (2024)
Major depression, as a clinical condition associated with the highest rate of disability worldwide, presents very particular contours when it affects the pediatric population. The biochemical and pathophysiological changes associated with depression are naturally influenced by socioeconomic aspects and family dynamics, which contributes to great heterogeneity and variability in the symptoms expressed by children and adolescents. The COVID-19 pandemic, following the implementation of the necessary measures to mitigate the virus infection, has worsened mental illness in the general population, including the pediatric population, significantly contributing to an increase in cases of anxiety, depression and even of post-traumatic stress. This review aims to systematize the pathophysiological aspects of depression that manifests early in life, as well as its current therapeutic context, shedding some light on pharmacogenetics and the way in which multimodal drugs are designed to be used in the pediatric population. A search was conducted in the PubMed and Google Scholar databases, and only articles written in English and Portuguese published in journals indexed to the Web of Science were included in this review, as well as current guidelines for pharmacological prescription in pediatric depression. The results made it possible to compile current data on the efficacy and safety of medications used to treat this clinical situation and discuss the current paradigm of mental health in pediatrics.